2010
DOI: 10.2478/v10055-010-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of indices for assessing the ecological potential of urban development

Abstract: Nowadays, the ecological evaluation of urban development has become compulsory, and a number of environmental indices have been introduced. In the present study, two most common environmental sustainability indices-ecological footprint and environmental sustainability-were applied for measuring the ecological possibilities of urban development. Moreover, the issues of the measuring principles, their disparities and direct application are discussed, and a short comparison of the indices is presented. Also, a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Estimating the size of an ecological footprint is a complex calculation involving many sectors of activity (Juščius & Dargienė, 2015;Staniūnas et al, 2010;Kitzes et al, 2007). Its concept has been extensively studied by many scholars interested in sustainable development but there are also many minus complexities (Kitzes et al, 2009;Vuuren & Smeets, 2000;Gao & Tian, 2016;Totha & Szigeti, 2016;Marrero et al, 2017;Wackernagel et al, 2004;Gu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the size of an ecological footprint is a complex calculation involving many sectors of activity (Juščius & Dargienė, 2015;Staniūnas et al, 2010;Kitzes et al, 2007). Its concept has been extensively studied by many scholars interested in sustainable development but there are also many minus complexities (Kitzes et al, 2009;Vuuren & Smeets, 2000;Gao & Tian, 2016;Totha & Szigeti, 2016;Marrero et al, 2017;Wackernagel et al, 2004;Gu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…introduction ecological studies have shown significant exposure-response relationships for adverse pollution effects in association with particulate mass concentrations (Poszyler-Adamska, Czerniak 2007;staniūnas et al 2010). Particulate matter has been associated with pollution and fate in urban storm water (Valentukevičienė, ignatavičius 2011).…”
mentioning
confidence: 99%
“…30% higher compared to that measured at Central streets (C1, C3). This site was strongly influenced by vehicle exhaust emissions (tchepel et al 2012) resulting from heavy traffic load (Baltrėnas, Vaišis 2006;Jankaitė et al 2008;staniūnas et al 2010).…”
mentioning
confidence: 99%